Analysis of Vitamin C Content in Ruku-Ruku (Ocimum tenuiflorum L.) Leaves - Salbia Salbia; Fatmah Dhafir; Abdul Ashari; Musdalifah Nurdin; Amalia Buntu; Manap Trianto (Biology, Medicine, & Natural Product Chemistry, 2026)
Ruku-ruku (Ocimum tenuiflorum L.) is widely recognized as a medicinal plant used in traditional medicine. The leaves are the most commonly utilized part of the plant, particularly for treating various health conditions such as fever, cough, joint and nerve pain, oral ulcers, tinea versicolor, nausea, and vomiting. Ruku-ruku leaves contain various essential nutrients, including calcium, iron, zinc, vitamin A, and vitamin C. This study aimed to determine the vitamin C content of ruku-ruku leaves. The research employed a quantitative descriptive method using the iodimetric titration technique. The samples consisted of young, mature, and old leaves collected from Tulo Village, Sigi Regency, Indonesia. Vitamin C content was measured with three replications for each sample. The results showed that the highest vitamin C content was found in young leaves, with an average value of 70.89 mg/100 g, followed by mature leaves at 54.18 mg/100 g and old leaves at 33.80 mg/100 g. Differences in vitamin C content were influenced by the level of leaf maturity, with younger leaves containing higher concentrations of vitamin C than older leaves.